EXERCISE 5 (a) Expand and simplify: \( \begin{array}{lllll}\text { (1) }(x+7)(x-7) & \text { (2) } & (x-3)(x+3) & \text { (3) } & (2 x-1)(2 x+1) \\ \text { (4) } & (9 x+4)(9 x-4) & \text { (5) } & (3 x-2 y)(3 x+2 y) & \text { (6) } \\ \left(4 a^{3} b+3\right)\left(4 a^{3} b-3\right) \\ \text { (7) } & \left(6-3 x^{4} y\right)\left(6+3 x^{4} y\right) & \text { (8) } & (3 x-2+y)(3 x-2-y)\end{array} \) \( \begin{array}{lll}\text { (9) } & \left(1-a^{4}\right)\left(1-a^{2}\right)\left(1+a^{2}\right) & \end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
Let’s expand and simplify those expressions step by step! (1) \( (x+7)(x-7) = x^2 - 49 \) (2) \( (x-3)(x+3) = x^2 - 9 \) (3) \( (2x-1)(2x+1) = 4x^2 - 1 \) (4) \( (9x+4)(9x-4) = 81x^2 - 16 \) (5) \( (3x-2y)(3x+2y) = 9x^2 - 4y^2 \) (6) \( (4a^3b+3)(4a^3b-3) = 16a^6b^2 - 9 \) (7) \( (6-3x^4y)(6+3x^4y) = 36 - 9x^8y^2 \) (8) \( (3x-2+y)(3x-2-y) = (3x-2)^2 - y^2 = 9x^2 - 12x + 4 - y^2 \) (9) \( (1-a^4)(1-a^2)(1+a^2) = (1-a^4)(1-a^2) = 1 - a^2 - a^4 + a^6 = 1 - a^4 + a^6 - a^2 \) Voilà! Each expression has been expanded and simplified.